Genetic Analysis of Marsh Spot Resistance in Cranberry Common Bean (Phaseolus vulgaris L.) - Jia, Bosen (Université d'Ottawa / University of Ottawa, 2022)
Cranberry common bean (Phaseolus vulgaris L.) is planted worldwide and consumed as a critical food source of human protein, fibre, carbohydrates, and minerals. Marsh spot (MS) is a physiogenic disorder which severely impacts seed quality in common beans. Previous studies indicate that MS involves a nutritional disorder caused by Mn deficiency. However, the inheritance and genetic mechanism of MS resistance are still not fully understood. To investigate the genetics of MS resistance, a population of 138 recombinant inbred lines (RILs) was developed from a bi-parental cross between a susceptible cultivar Messina and a resistant cultivar Cran09. The population and its two parents were evaluated for MS resistance during five consecutive years from 2015 to 2019 in both sandy and heavy clay soils in Morden, Manitoba, Canada. The severities of MS were rated and subsequently converted to MS resistance index (MSRI) and MS incidence (MSI). Statistical analyses indicated that MSI and MSRI were highly correlated (r = 0.96-0.99) and had high broad-sense heritability (H²) of 86.5% and 83.2%, respectively. Joint segregation analysis (JSA) of 18 phenotypic datasets from five years and two soil types showed that MS resistance was controlled by four major genes with genetic interactions - one of which may suppress the additive effect of the other three genes. To identify the quantitative trait loci (QTL) and the candidate genes associated with the MS resistance, the 138 RILs and the two parents were sequenced using genotyping by sequencing approach. A total of 52,676 SNPs were detected. After further filtering with a threshold of minor allele frequency > 0.01 and call rate > 20%, 2,061 SNPs were retained and then imputed for genetic map construction and QTL mapping. A genetic map consisting of 2,058 SNP markers on 11 linkage groups or chromosomes was constructed, which covered 1,004 recombination blocks with a total length of 6,449 cM and an average block of 6.42 cM. Three linkage map-based QTL-mapping models ICIM-ADD, ICIM-EPI, and GCIM and one genome-wide association study (GWAS) model RTM-GWAS for 18 phenotypic datasets from different years and soil types were used for identification of QTL. A total of 36 QTL, including 21 of additive and 15 of epistatic effects, were identified. Functional gene annotation analysis revealed 151 Mn-related candidate genes across the common bean reference genome and 17 of them harbored the six QTL discovered in this study. In conclusion, MS resistance in common bean is a highly heritable trait and controlled by several major and minor genes. The results of JSA and QTL mapping advance the current understanding of the genetic mechanisms of MS resistance in cranberry common bean, and provide additional resources for application in genomics-assisted breeding and potential isolation and functional characterization of the candidate genes.
Keywords: marsh spot disease; cranberry common bean; joint segregation analysis (JSA); QTL mapping; genotyping by sequencing (GBS); single nucleotide polymorphism (SNPs); genome-wide association study (GWAS); Phaseolus vulgaris